Prinsip Prinsip Dasar Muamalah Dalam Islam - Idris Siregar; Ucok Kurnia Meliala Hasibuan; Hazriyah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
. Discussion of the basic principles of muamalah in Islam includes learning about the rules that regulate relationships between humans regarding property, rights and obligations. The aim of the basic principles of muamalah is to create justice and benefit in social life. This research aims to review further the basic principles of muamalah in Islam which serve as guidelines for Muslims in carrying out economic and social activities. By applying these principles, it is hoped that a just, prosperous and blessed society can be achieved. This research uses a qualitative approach with the library search method. The descriptive qualitative approach used aims to explore and explain existing phenomena by relying on sources of information from various sources such as books, journals, digital databases and other literature. The main aim of this research is to provide insight that the basic principles of muamalah in Islam do not only limit halal and haram rules in economic activities, but also guide Muslims in building economic interactions that are fair, blessed, and in line with Islamic values.